2011
DOI: 10.1002/per.775
|View full text |Cite
|
Sign up to set email alerts
|

The closed mind: ‘Experience’ and ‘cognition’ aspects of openness to experience and need for closure as psychological bases for right–wing attitudes

Abstract: Openness to Experience and Need for Closure (NFC) are dispositional variables related to social-cultural right-wing attitudes. The present study investigated their joint effects. Factor analysis revealed an 'experiential' dimension with high loading openness items, and a 'cognition' dimension with high loadings for most NFC items and about a quarter of the openness item set. The experiential openness items were weakly related to right-wing attitudes, demonstrating little predictive value. Conversely, the cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 63 publications
2
66
1
4
Order By: Relevance
“…Yet, NFC is distinct from these alternative notions by dint of its explicitly motivational rather than cognitive or personality basis (for more elaborate arguments on this point, see Kruglanski, 2004;. Moreover, empirically, NFC yields relatively modest relations with these variables (usually <j0.30j) and, as we note at a later juncture, yields unique relations with third variables (see e.g., Onraet, Van Hiel, Roets, & Cornelis, 2011;Roets & Van Hiel, 2011b). …”
Section: The Nfc Constructmentioning
confidence: 71%
See 3 more Smart Citations
“…Yet, NFC is distinct from these alternative notions by dint of its explicitly motivational rather than cognitive or personality basis (for more elaborate arguments on this point, see Kruglanski, 2004;. Moreover, empirically, NFC yields relatively modest relations with these variables (usually <j0.30j) and, as we note at a later juncture, yields unique relations with third variables (see e.g., Onraet, Van Hiel, Roets, & Cornelis, 2011;Roets & Van Hiel, 2011b). …”
Section: The Nfc Constructmentioning
confidence: 71%
“…Consistent with this parallelism, a number of studies have shown dispositional NFC to be strongly related to various measures of blatant, subtle, and modern forms of racial prejudice (e.g., Onraet et al, 2011;, 2011aVan Hiel et al, 2004) and even to implicit measures of racism (Cunningham, Nezlek, & Banaji, 2004). Moreover, NFC has also been linked to other targets of prejudice, for example, groups based on sexual orientation or identity (Brandt & Reyna, 2010;Tebbe & Moradi, 2012).…”
Section: Nfc and Prejudicementioning
confidence: 79%
See 2 more Smart Citations
“…The importance of personal threat consequences in explaining ethnic prejudice, rather than right-wing attitudes, might be explained by the fact that ethnic prejudice is more affectively driven, whereas right-wing attitudes, such as RWA and SDO, have a more cognitive outlook (e.g., Onraet, Van Hiel, Roets, & Cornelis, 2011). It may be expected that the experience of potential personal problems may evoke strong negative emotions, such as fear and anxiety, leading to higher levels of ethnic prejudice (see Kossowska, Bukowski, & Van Hiel, 2008).…”
Section: Discussionmentioning
confidence: 99%